Economic Inequality among Districts in Keerom, Papua, Indonesia - Nuralam, Nuralam (Journal of Social and Development Sciences, 2015)
This research described about economics growth and economic imbalance among districts in Keerom regency. The aim of this research is (i) to explain the pattern of economics growth per district in Keerom regency (ii) to illustrate the imbalance among districts in Keerom regency (iii) to examine Kuznets hypothesis about the Inverted of U in Keerom regency. Analysis technique has been applied is Klassen typology, Williamson’s index and Pearson’s correlation. In this research, Klassen typology is divided by two quadrants. The result of this research showed the low of Williamson’s index and there was not applicable result on analysis with the Inverted of U by Kuzrets hypothesis. This research is expected to be a useful input for government, particularly for local government of Keerom regency.